Impacts of an Eruption on Cold-Seep Microbial and Faunal Dynamics at a Mud Volcano - Girard, Fanny; Sarrazin, Jozée; Olu, Karine (Frontiers in Marine Science, 2020)
Cold seeps are widespread in the deep sea and, like other chemosynthesis-based ecosystems, often host high faunal biomass. Temporal changes at seeps have been inferred by comparing communities at different successional stages; nonetheless, temporal studies in seep ecosystems are rare. Using data collected as part of a benthic observatory, we characterized intra-annual microbial and faunal dynamics in a microbial mat habitat on the Håkon Mosby mud volcano (1256 m depth; Barents Sea), and evaluated the effects of a mud eruption on the biota. Video sequences recorded twice daily for 4.5 months with an autonomous imaging module were analyzed to quantify changes in microbial mat cover and megafaunal density and behavior. In addition, time series data for pressure, bottom currents, and seabed temperature were analyzed to characterize environmental changes. Of the five taxa observed on the video footage, the zoarcid Lycodes squamiventer, the pycnogonid Nymphon macronyx, and the skate Amblyraja hyperborea were the most common. Zoarcids made frequent incursions on microbial mats, but were more often documented on the adjacent sediments. The cyclic behavior of common trends identified between microbial mat cover, zoarcid densities and abiotic variables using dynamic factor analysis (DFA) suggested that seep ecosystem dynamics at the Håkon Mosby mud volcano may be modulated by tides and the activity of the volcano. Moreover, the eruption that occurred about two months after the start of the study had a significant impact on faunal densities, microbial activity, and environmental variables. The eruption was preceded by a steady increase in seabed temperatures, density of small holes (indicative of gas emissions), and microbial mat cover. It was followed by 3- and 5-fold increase in zoarcid and pycnogonid densities, respectively. To our knowledge, this study is the first to analyze intra-annual temporal data in a cold-seep ecosystem and to present data on the effects of a mud eruption on seep microbial and faunal dynamics. Our results provide the first insight into ecosystem dynamics at a high-latitude cold seep and highlight the need to collect high-resolution temporal data to evaluate seep communities’ response to a warming Arctic and their potential role in mitigating methane emissions.